Kinect-Based Exergames Tailored to Parkinson Patients. (30th October 2018) - Pachoulakis, Ioannis; Papadopoulos, Nikolaos; Analyti, Anastasia
Abstract : Parkinson's disease (PD) is a progressive neurodegenerative movement disorder where motor dysfunction gradually increases. PD-specific dopaminergic drugs can ameliorate symptoms, but neurologists also strongly recommend physiotherapy combined with regular exercise. As there is no known cure for PD, traditional rehabilitation programs eventually tire and bore patients to the point of losing interest and dropping out of those programs just because of the predictability and repeatability of the exercises. This can be avoided with the help of current technology, character-based, interactive 3D games promote physical training in a nonlinear fashion, and can provide experiences that change each time the game is played. Such "exergames" (a combination of the words "exercise" and "game") challenge patients into performing exercises of varying complexity in a playful and interactive environment. In this work we present a Unity3D-based platform hosting two exergames tailored to PD patients with mild to moderate symptoms. The platform employs Microsoft Kinect, an affordable off-the-shelf motion capture sensor that can be easily installed in both home and clinical settings. Platform navigation and gameplay rely on a collection of gestures specifically developed for this purpose and are based upon training programs tailored to PD. These gestures employ purposeful, large-amplitude movements intended to improve postural stability and reflexes and increase upper and lower limb mobility. When the patient's movements, as detected by Kinect, "match" a preprogrammed gesture, an onscreen 3D cartoon avatar responds according to the game context at hand. In addition, ingame decision-making aims at improving cognitive reaction.